2013 IEEE Transportation Electrification Conference and Expo (ITEC) 2013
DOI: 10.1109/itec.2013.6574494
|View full text |Cite
|
Sign up to set email alerts
|

An advanced electro-thermal cycle-lifetime estimation model for LiFePO<inf>4</inf> batteries

Abstract: Electric vehicles (EVs) have been considered as one of the effective solutions to current energy and environment concerns. One of the challenges regarding the energy storage system (ESS) of today's electric vehicles, which are batteries, is the capacity fade. It is of great importance to identify and analyze the factors contributing to the capacity loss and predict the cell degradation. In this manuscript, an advanced systematic Lithium iron phosphate (LiFePO 4 ) battery cell model is proposed to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In addition, the battery remaining state-of-health (SOH) after 10 years are estimated based on previous work in [26] and presented in Table V. Here, a daily commute is constructed as a repeated sequence of the corresponding drive cycles to cover 40 miles.…”
Section: B Results and Comparisonsmentioning
confidence: 99%
“…In addition, the battery remaining state-of-health (SOH) after 10 years are estimated based on previous work in [26] and presented in Table V. Here, a daily commute is constructed as a repeated sequence of the corresponding drive cycles to cover 40 miles.…”
Section: B Results and Comparisonsmentioning
confidence: 99%
“…Battery models are essential to estimate the lifetime accurately under various operation conditions. Therefore, the model-based studies [155][156][157][158][159] are carried out by researchers to investigate the charge/discharge behavior and the remaining life of batteries. Vincenzo et al [155] presented a study that deals with the life estimation of lithium batteries for PHEVs under vehicular operation and real driving cycles.…”
Section: Battery Life Estimationmentioning
confidence: 99%
“…Filippi et al [157] suggested similar model-based methodology like [156] and performed a comprehensive simulation study to estimate the battery residual life under real-world driving conditions. A sophisticated electro-thermal model of LiFePO 4 battery is enforced in [158] with the aim of estimating battery lifetime and analyzing the impact of different factors on the battery lifetime.…”
Section: Battery Life Estimationmentioning
confidence: 99%
“…4, with the proposed control strategy implemented in the battery/UC HESS, the battery power magnitude is reduced by 58.44% in comparison to the batteryonly ESS. In order to estimate the battery lifetime extension, a battery degradation model given in [13] is utilized. In this model, the temperature, the depth-of-discharge (DOD) and the C-rate effects on capacity loss are considered.…”
Section: B Power Split In Hessmentioning
confidence: 99%